Review Artikel: Kajian Senyawa Fitokimia dan Aktivitas Farmakologi Antidiabetes dari Syzygium cumini - Rustamsyah, Ardi; Perdana, Farid; Zulfakor, Dava; Kusmiyati, Mimin (LP4M STIKes Karsa Husada Garut, 2023)
Introduction: Jamblang is a plant from the Myrtaceae family. It can be used as a traditional medicine, one of which can treat diabetes. The purpose of this review is to determine the phytochemical compounds of Syzygium cumini that have antidiabetic activity. Methods: The methods used in the preparation of this review article are to search for various sources that discuss antidiabetic activity and phytochemical studies of Syzygium cumini. Results: The results of the review that have been carried out explain the in vitro and in vivo testing of antidiabetic activity on the inhibition method and the induction method, resulting in jamblang potentially as an antidiabetic. Conclusion:The results of the review that have been carried out explain the phytochemical study using HPLC method there are groups of flavonoid, phenolic, and phenylpropanoid compounds, and on the TLC method there are groups of terpenoids. Oleic acid and ursolic acid compounds have antidiabetic activity.